Teenagers’ Safety Smartphone Use Model Based on Health Promotion Theory - Rizki Fitryasari; Rr Dian Tristiana; Ah Yusuf (Jurnal Ners, 2021)
Introduction: Smartphones and teenagers in the age of technology are two very close things. Uncontrolled use of smartphones can create serious problems for teenagers, namely addiction. This research aims to build a safe smartphone use model for teenagers using a health promotion theory.Methods: This study was an explanatory study with a cross-sectional approach. The study population was 11-18 year old teenagers in Surabaya, Indonesia who use smartphones actively. The respondents were 185 teens recruited by simple random sampling. Variables include teenager factors, technology factors, environmental factors, teenagers’ thinking, self-control, commitment, and the level of smartphone use. The instrument used was an on-line questionnaire distributed through social media and then analyzed with partial least squares. The statistical afforded material for focus group discussion followed by 15 teenagers, 15 parents and 5 health workers in order to improve the model.Results: The results showed that the level of smartphone use was affected by self-control (t=2.303; p=0.022) and commitment (t=2.967; p=0.003). Self-control is influenced by adolescent factors (t=3.065; p=0.002), environmental factors (t=2.934; p=0.004) and teenagers’ thinking (t=2.522; p=0.012), also self-control affects teenagers’ commitment for using smartphones (t=3.953; p=0.000).Conclusion:The model formed emphasizes the importance of establishing self-control through adolescent thinking and environment factors so that they can commit to using smartphones safely